Women and Gender in the Early Modern Low Countries - Joan Moran, Sarah; Pipkin, Amanda C. (Studies in Medieval and Reformation Traditions, 2019)
Women and Gender in the Early Modern Low Countries, 1500-1750 brings together research on women and gender across the Low Countries, a culturally contiguous region that was split by the Eighty Years' War into the Protestant Dutch Republic in the North and the Spanish-controlled, Catholic Hapsburg Netherlands in the South. The authors of this interdisciplinary volume highlight women's experiences of social class, as family members, before the law, and as authors, artists, and patrons, as well as the workings of gender in art and literature. In studies ranging from microhistories to surveys, the book reveals the Low Countries as a remarkable historical laboratory for its topic and points to the opportunities the region holds for future scholarly investigations. Contributors: Martine van Elk, Martha Howell, Martha Moffitt Peacock, Sarah Joan Moran, Amanda Pipkin, Katlijne Van der Stighelen, Margit Thøfner and Diane Wolfthal.